2015
DOI: 10.4238/2015.december.7.22
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor-α 308G/A polymorphism with urogenital cancer risk: a systematic review and meta-analysis

Abstract: ABSTRACT. We integrated all the eligible studies and investigated whether the TNF-α 308G/A polymorphism correlates with urogenital cancer risk. Tumor necrosis factor-α (TNF-α) is a risk factor for some urogenital cancers; however, in prostate and bladder cancers the results are controversial. PubMed, EMBASE, Web of Science, the Cochrane Library, the Chinese Biomedical Literature Database, and the Wanfang Database were searched for all case-control studies on the relationship between the TNF-α 308G/A polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…[ 8 , 9 ] Several studies have indicated that several polymorphisms in the promoter region of TNF-α are associated with the risk of some types of cancers, such as urogenital cancer, non-Hodgkin lymphomas, gastric cancer, and breast cancer. [ 10 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 , 9 ] Several studies have indicated that several polymorphisms in the promoter region of TNF-α are associated with the risk of some types of cancers, such as urogenital cancer, non-Hodgkin lymphomas, gastric cancer, and breast cancer. [ 10 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to the current meta-analysis, there was a variety in terms of s1799724 and rs1800629 polymorphisms of the TNF-α gene distribution in the different ethnicity. Compared to the previously published meta-analyses [24,25] there are more studies included in the current meta-analysis, and the overall sample size is larger; therefore, our findings are more precise and reliable. In addition, the present meta-analysis there is the only study that has assessed both s1799724 and rs1800629 polymorphisms association with cervical cancer simultaneously.…”
Section: Discussionmentioning
confidence: 61%
“…1). found that the TNF-α 308G>A polymorphism was significantly associated with CC risk [57]. Furthermore, in another meta-analysis Jin et al have found that -308 G>A and -238 G>A polymorphisms of TNF-α gene may confer susceptibility to CC in an ethnic-specific fashion [55].…”
Section: Breast Cancermentioning
confidence: 99%